An Assessment to Measure Problem-Solving Ability and Science Process Skills: A Feasibility Test - Faila, Rohaya Evatri; Supahar, Supahar; Pebriana, Irvany Nurita (Jurnal Pendidikan Fisika, 2025)
The ability to solve problems and apply scientific processes is a critical component of 21st-century education, especially within the context of the Indonesian "Merdeka" curriculum, which promotes independent and adaptive learning. However, traditional assessment methods fail to capture these competencies adequately. This study aims to determine the feasibility of an assessment instrument designed to measure high school students' problem-solving ability and science process skills. The instrument was developed using Istiyono’s test development model and focused on the test trial stage, which involves expert validation, empirical analysis, reliability testing, and item difficulty analysis. Using Istiyono’s model, the development focused on expert validation, empirical testing, and item analysis. A total of 252 students from six high schools in Yogyakarta and surrounding regions participated in the study. The content validity was assessed using Aiken's V, showing all items to be valid. Content validity, evaluated using Aiken’s V, indicated all items were valid. Empirical validation using the QUEST program yielded INFIT MNSQ values of 0.99 ± 0.81 for problem-solving and 1.01 ± 0.21 for science process skills, confirming item validity. Reliability coefficients ranged from 0.61 to 0.97, indicating high reliability. The difficulty level of items was distributed across easy, medium, and difficult categories. These findings support the feasibility of the assessment instrument in evaluating students’ higher-order thinking skills. The findings demonstrated the instrument’s suitability for assessing complex cognitive and inquiry-based skills. The validated instrument offers practical implications for educators to improve learning through formative assessment aligned with curriculum goals.